DB2 UDB for Linux on iSeries implementation guide - Johng, Yessong (IBM, 2004)
This IBM Redbooks publication discusses DB2 UDB for Linux on iSeries. We provide the installation and configuration steps for DB2 UDB for Linux on iSeries. We also present connectivity scenarios between OS/400 resources and Linux resources. With V8.1, DB2 UDB for Linux is available for running in a Linux partition on an IBM eServer iSeries system. Linux is one of the fastest growing operating systems in the industry today. Linux is quickly becoming a key enabler for e-business applications that are demanding more robust local database capabilities. Applications running in the Linux partition can certainly leverage DB2 UDB for iSeries through a variety of interfaces (DB2 Connect, JDBC, ODBC), and this is an excellent choice to leverage the low administration overhead, autonomic computing, and security benefits provided by DB2's tight integration with OS/400. DB2 for Linux is an excellent choice to support Linux (or other client/server) applications when there is a need to have local data storage within the Linux application environment or to leverage specific features of DB2 UDB V8 such as Federated Database or Microsoft .NET Framework support.
"April 2004.". - "This edition applies to DB2 UDB for Linux on iSeries V8.1.2 and OS/400 V5R2.". - "How to install and configure DB2 UDB for Linux on iSeries. Understanding DB2 Connect and its features. Database access scenarios from Linux applications.". - Title from title screen. - Title from website (viewed January 3, 2006). - Includes bibliographical references and index
Keywords: IBM Database 2; Linux; Database management; Bases de données; Gestion